Agency and signification in learning with digital technologies: A theoretical approximation of actor-network theory and representational perspectives - Schiavetto, Stefano; Schnaider, Karoline (Proceedings of the International Conference on Networked Learning, 2024)
This paper put an approximation of Actor-Network Theory – ANT (cf. Callon & Latour, 1981; Latour, 1988; Latour, 1993; Latour, 1994) and representational philosophies deriving from the social semiotic multimodal theories (e.g., Hodge & Kress, 1988; Kress, 2010; Kress & van Leeuwen, 2021; van Leeuwen, 2005) to the fore to conceptualize how meaning-making (known as sign-making, learning, the process of signification, Bateman, 2018; Bezemer & Kress, 2016; Kress, 2010) via technologies come about from the technologies’ various prompts. It is essential to recognize how representations such as semiotic resources – here, technologies and sign systems – have agency to form social practices. They are agentively selected, interpreted, and acted upon by the user into meaning-making activities (Jewitt, 2008, 2009, 2014). The technologies’ front- and back-end properties’ semiotic regimes (van Leeuwen, 2005; Djonov & van Leeuwen, 2018a) in different configurations can function as actants by symmetrically translating interests between humans and non-humans, into hybrid existences (Callon & Latour, 1981; Latour, 1994). Humans and technical objects are not rigid and independent substances (Platonic) but beings in constant (re)associations, which modify their existence (Callon & Latour, 1981; Latour, 1994). In that sense, Callon and Latour’s claims can be understood in line with the genesis and development of representations that, from a historical epistemological perspective (Wartofsky, 1979), are in constant (re)associations by technologies, cultures, social practices, and humans. As humans mediate by means of their representations (Wartofksy, 1979), the representations are re-shaping and re-shaped through the history of reproduction that impacts interaction, meditation, and meaning-making (Kress, 2010; van Leeuwen, 2005; Wartofsky, 1979). The purpose of this paper is to briefly sketch a future research aspiration striving to theoretically approximate the ANT and representational philosophies and examine what kind of agency digital technologies impose on the users and how the users draw upon that imposition in their meaning-making. Crucially, such a reflection can heighten current understandings of the intricate relationships and networks created by humans and digital technologies in contemporary learning settings such as school to better appreciate students’ digital learning from a representational agency perspective integrating the “signifieds-in-transformation” and “actants.” In preparation for future research studies, the following research question guides the theoretical explorations: who acts in the process of signification in learning activities with digital technologies?